Pengaruh Corporate Governance Index terhadap Ketepatan Waktu Corporate Internet Reporting (Studi Empiris pada Perusahaan Peserta Corporate Governance Perception Index) - Cahyo Indra Dharmawan; Ihyaul Ulum; Endang Dwi Wahyuni (Kompartemen : Jurnal Ilmiah Akuntansi, 2017)
This study aimed at providing empirical evidence of the influence of corporate governance index on the punctuality of corporate internet reporting in companies registered in the Corporate Governance Perception Index (CGPI) in 2015. Data collection technique used was secondary data in form of CG index (corporate governance) and emails from IICG's official website, www.iicg.org and punctuality data to figure out which companies are implementing corporate internet reporting. The sample in this research was 30 companies registered in CGPI 2015. The analysis method used was descriptive statistic and logistic regression with SPSS software version 21. The result of logistic regression analysis indicated that corporate governance index (CGI) had a significant influence on the punctuality of corporate internet reporting (CIR).Keywords: corporate governance index, corporate governance perception index, corporate internet reporting, punctuality.